KEPEMIMPINAN TRANFORMASIONAL MENINGKATKAN PRILAKU KERJA INOVATIF DAN KINERJA PEGAWAI DI KANTOR PELAYANAN PUBLIK (Studi Kasus Kantor Pelayanan Pajak (KPP) Pratama Bengkulu Satu) - Alexsander; Wasi Seto Wasisto; Aprianty, Henny (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2023)
The purpose of this study is to analyze and explain the variables that affect public administration tasks. Transformational leadership is a variable which is the most important and significant dependent variable in this study. In addition to the transformational leadership studied, the variables of organizational work culture, equipment efficiency, and innovative work behavior are also included. This research was designed using quantitative research. The study was conducted from January to June 2023 at the Pratama Bengkulu Tax Service Office (KPP), a vertical division of the Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia. 87 employees and a sample of 80 respondents participated in this study. To analyze the data, the SEM (Structural Equation Model) model was used which was developed through a questionnaire that was tested for validity and reliability. The process of data analysis is carried out using assumptions and statistical techniques and is supported by the SmartPLS 3.2.9 application. The research results show that Transformational Leadership increases innovative work behavior and organizational performance.